Motor performance and learning difficulties in schoolchildren aged 7 to 10 years old Desempenho motor e dificuldades de aprendizagem em escolares com idades entre 7 e 10 anos - Silva J.* (2011)
The general objective of this study was to evaluate the motor performance of children with and without learning difficulty indicatives. Took part in the study 406 students aged 7 to 10 years old, being 231 girls (56.9%) and 175 (43.1%) boys enrolled in a municipal public school in São José, Santa Catarina, Brazil. The indicative of learning difficulties was verified through the TDE, while motor performance was evaluated with the MABC. Boys without learning difficulties had better performance in the majority of the abilities evaluated, beyond an association between the indicative of motor problems with learning difficulties towards writing, arithmetic, reading, and in general. On the other hand, female students of the sample with and without any indicative of learning difficulties did not differentiate themselves as to motor abilities evaluated, with an association merely between the indicative of motor problems and reading problems. Based on the differences identified between girls and boys, results call attention to the need for future research in this area, considering gender as a differential variable in this relationship. © FTCD/CIDESD.